2022
DOI: 10.2196/37233
|View full text |Cite
|
Sign up to set email alerts
|

Drug Recommendation System for Diabetes Using a Collaborative Filtering and Clustering Approach: Development and Performance Evaluation

Abstract: Background Diabetes is a public health problem worldwide. Although diabetes is a chronic and incurable disease, measures and treatments can be taken to control it and keep the patient stable. Diabetes has been the subject of extensive research, ranging from disease prevention to the use of technologies for its diagnosis and control. Health institutions obtain information required for the diagnosis of diabetes through various tests, and appropriate treatment is provided according to the diagnosis. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Their study found that individual treatment effects resulted in recommendations that were significantly better than the usual treatment in reducing stroke and the composite end point of stroke and major bleeding. In addition, a diabetes drug recommendation model by Morales et al, 9 which uses a collaborative filtering and clustering approach, was reported to help health personnel determine appropriate prescriptions for diabetes management. The prediction results of this recommender system have good results, providing a new perspective for diabetes treatment and clinical management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study found that individual treatment effects resulted in recommendations that were significantly better than the usual treatment in reducing stroke and the composite end point of stroke and major bleeding. In addition, a diabetes drug recommendation model by Morales et al, 9 which uses a collaborative filtering and clustering approach, was reported to help health personnel determine appropriate prescriptions for diabetes management. The prediction results of this recommender system have good results, providing a new perspective for diabetes treatment and clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine learning has been studied in precision medication to help decision making in an individual patient. [9][10][11] Although results from large population-based studies provide average treatment effects, physicians are unsure to make the best strategy for a single patient due to potential individual heterogeneity. Machine learning can be used to approach complex clinical situations and train predictive models based on single individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, collaborative filtering and clustering can be used to develop a drug recommendation system that suggests medications for patients with diabetes by comparing a specific patient profile with those of patients with similar characteristics [ 18 ]. Similarly, collaborative filtering and clustering can be used to develop a recommender system for patients with cardiovascular diseases [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another major component of these efforts, however, tries to achieve intelligent treatment recommendations in a data-driven manner based on statistical rules learned from big clinical data via diversi ed machine learning methods, for example, clustering analysis, logistic regression, decision tree, tabular Q-learning, and so on. It has been successful in treatment recommendation and optimization for mobilization in ICU 10 , diabetes 11 , atrial brillation 12 , postmenopausal osteoporosis 13 , basal cell carcinoma 14 , breast cancer 15 , cardiovascular disease 16 , and ovarian cancer 17 . Moreover, as a typical representative of machinelearning-driven AI systems for automated disease diagnosis and treatment recommendation, the famous commercialized product Watson for Oncology designed by International Business Machine (IBM) has been proven to be reliable in treatment recommendations for various types of cancer, e.g., breast cancer 18 and lung cancer 19 .…”
Section: Introductionmentioning
confidence: 99%